The critical period for grain yield in chia (Salvia hispanica) - Diez, Josefina; Anuch Tiranti, Juan Valentín; Sadras, Victor Oscar; Acreche, Martin Moises (CSIRO, 2022)
Chia (Salvia hispanica L.) grain is rich in omega-3 and omega-6 fatty acids, which are important for human nutrition and prevention of cardiovascular disease, as well as dietary fibre and quality protein. Demand for chia grain is increasing worldwide driven by the interest in functional food; however, large gaps exist in our understanding of chia physiology. The objective of this study was to determine the critical period for grain yield in chia. A field experiment was conducted under well-watered conditions during four growing seasons, using sequential shading periods of 7–10 days during the season. Yield of unshaded controls varied from 1418 to 2148 kg ha–1 among seasons. Chia’s critical period for grain yield spanned from 550 degree-days before flowering to 250 degree-days after flowering. Seed number fully accounted for reductions in grain yield, with no responses in grain weight to shading. Shading from 550 to 250 degree-days before flowering reduced yield by as much as 40% and this reduction was associated with reductions in the number of verticillasters on second and third order branches. Shading from 50 degree-days before flowering to 250 degree-days after flowering reduced yield by at least 20% and this reduction was associated with reductions in both the number of verticillasters on second and third order branches and the number of grains per verticillaster on branches of all orders. The findings from this study will aid development of management practices to avoid stresses during periods when grain yield would be penalised, and will contribute to breeding for yield potential and stress adaptation by targeting the critical physiological stages.